O que vem aí: estratégias de divulgação da programação - Souza, Gabriel (2015)
In recent years, within the media context, television has faced several interferences, whether by the advance of digital technologies, or by the falling audience ratings, forcing broadcasters to adopt new communication strategies for the viewers. This paper proposes a reflection on this issue, focusing on the study of the productions, aimed at publicizing the station´s grid, for viewers, and for the valuing of the company. Thus, the purpose of this research is to examine the set of self-promotional actions specifically aimed at the launch of annual programs of open television stations. For this, the analysis process is founded on the theoretical and methodological contributions of European inspired semiotics and the extension proposed by his successors, to the attempt of describing and explaining what the televisual texts of Rede Globo say and how they do to say so. This implies on the recognition of communicative and discursive strategies used in the production of these texts, in a motion that clearly combines the promotions and the self-promotion of the broadcasters. The corpus of analysis involves five pieces developed by the station, in a period of ten years. The choice of TV Globo is due to the nature of the commercial and vehicle of communication, which forces the company to develop the function of promoting and above all, self-promoting itself, attracting the attention of the viewers and selling space to advertisers and finally, ensuring its very survival.